Leonardo : rivista d'idee - Papini, Giovanni; Prezzolini, Giuseppe (Firenze : Vallecchi, 1903)
Leonardo was an Italian philosophy magazine published in the early twentieth century in Florence, Italy, between 1903 and 1907. It was one of the publications started by Giovanni Papini and contributed by Giuseppe Prezzolini. (wikipedia)
Italiaans
Tijdschriften
Keywords: Doudelet, Charles